Estudio de factibilidad económica y financiera para la instalación de una planta productora de zumos de maracuyá en la comuna Salanguillo de la provincia de Santa Elena - Machado Ruiz, Julio César (2015)
In the province of Santa Elena, the Colonche Salanguillo parish in the commune, there is a population engaged in agricultural planting tomatoes, peppers, onions but in particular the lanting of the passion fruit is a fruit that does not need much water, or much fertilizer hich will benefit the Salanguillo commune. Passion fruit is of tropical origin, the fruits of particular intense flavor and high acidity, ery popular in the American countries, Europe and Asia where the demand with great interest... …..